Methodological basis for the formation of physical culture personality - I.V. Ivanii (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose : to analyze the phenomenon of physical culture of the person subject to the methodological approaches its formation in the system of physical education. Material : analyzed 20 literature resources. Results : theoretical analysis possible to trace the emergence of approaches to physical training as a spiritual and physical phenomenon. Defined by its focus on the social and personal problems. Also identify the goals, objectives, content and conditions of physical education. Formulated conceptual idea: the construction of projective models of formation of physical culture of the person is determined by their axiological, anthropological and ontological components (in some combination of the two interrelated areas of personal development as a body-spirit nature and culture). It is shown that the real number of different models of targets and mechanisms to achieve them. The models are defined stages of individual, social and cultural development of the individual. Models include adaptation, socialization, self-actualization and inculturation. Conclusions : the formation of physical culture of personality based on modern concepts of the general theory of humanistic culture, the theory of human action. This work takes into account the philosophical, pedagogical and psychological aspects. Definition of methodological approaches allows us to construct the projective model of the formation of personality and physical culture reorientation teaching activities in this direction.